IN DEVELOPING SPEAKING SKILLS IN ENGLISH AMONG SCHOOL STUDENT PROBLEMS - Yoqubjonova Dilfuza Mo’minjon qizi (Journal of Applied Science and Social Science, 2026)
This study examines the key challenges in developing speaking skills in English among school students. It explores linguistic, psychological, and pedagogical factors that influence students’ oral communication abilities. The findings reveal that limited vocabulary, grammatical difficulties, and language anxiety significantly hinder speaking performance. Additionally, traditional teaching methods and lack of real-life practice opportunities further restrict students’ progress. The study highlights the effectiveness of communicative teaching approaches, supportive classroom environments, and the integration of digital tools in improving speaking skills. It concludes that a comprehensive, student-centered approach is essential for enhancing students’ fluency, confidence, and overall communicative competence.